Synergism Between Water Management and Phosphorus Supply Enhances the Nodulation and Root Growth and Development of Chinese Milk Vetch (Astragalus sinicus L.) - Sun, Zhengguo; Yi, Mingxuan; Liu, Xinbao; Yixin, Shen; Li, Jianlong (Frontiers in Plant Science, 2022)
The response of root development and nodule formation of the manure crop Chinese milk vetch to different levels of soil moisture and phosphorous (P) fertilizer remains unclear. In this study, a pot experiment was performed to trace the root growth and nodule formation of Chinese milk vetch at the seedling, branching and full-flowering stages, under various soil moisture gradients [25% (W1), 50% (W2), 75% (W3), and 100% (W4) of the maximum field water-holding capacity] and P levels [0 (P0), 30 (P1), 60 (P2), and 90 (P3) kg hm–2]. The root/shoot ratio, root vitality, number of nodules, nodule weight, and nitrogenase activity were affected remarkably by soil moisture or the level of added P across the whole stage. Differences were found in the interaction effect between soil moisture and added P on the characteristic indices of the root and nodule at the different growth stages. There were obvious differences in root activity and nitrogenase activity at seedling stage, but no evident differences were found in other indices. Certain differences were also found in the indicators mentioned above at the branching stage. W1P0 and W2P0 showed the highest root/shoot ratio, W2P2 and W3P2 resulted in the highest root activity; W3P3 and W3P2 had the highest number and weight of nodules; and W3P2, W2P2, and W3P1 had higher nitrogenase activity than the other treatments at the full-flowering stage. The application of P at 60 kg hm–2 and the relative soil moisture of 75% was the best P-water combination suitable for the root development, nodule formation, and nitrogen fixation of Chinese milk vetch. This study will provide a theoretical basis for the production of this plant by managing the synergistic interaction between P fertilizer and soil moisture.